Exports of Manufactures by Developing Countries: Emerging Patterns of Trade and Location. - Lall, S (1998)
Developing countries are rapidly increasing their shares of manufactured trade, not just in labour-intensive products, but also in capital- and skill-intensive ones; their shares are rising particularly rapidly in the high-technology area. However, manufactured exports remain highly concentrated in the developing world, with a few countries dominating all forms of export. Within the successful exporting countries, there are significant differences in the 'technology content' of exports. These trends are difficult to explain with received trade theory, even taking human capital into account, or with reference to broad economic policies: it is useful to bring in 'learning,' along with scale economies, increasing returns, and agglomeration as determinants of comparative advantage. These factors imply market failures, and so a role for policy in developing genuine comparative advantages. This article suggests that emerging trade and location patterns in the developing work are explained by market imperfections and government policies to overcome them.